Berkarya Tanpa Menyakiti: Edukasi Pencegahan Perundungan untuk Mewujudkan Lingkungan Sekolah yang Aman - Rima Annisa Balkis; Nathaniel Julistyo Respati; Selvy Dwi Arianing Tyas; Amalia Sukasah Putri; Alifiandra Rizki Ramadhan; Azka Hilkar Hendrianto; David Abraham Mewengkang (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Bullying remains a prevalent issue in school environments and negatively affects students’ well-being and learning comfort. This educational activity aimed to improve students’ understanding and awareness of bullying and the importance of polite language in creating a safe school environment. The method involved educational counseling through material presentation, interactive discussions, and evaluation using pretests and posttests. The activity was conducted at SMK Dr. Soetomo with students from the PSPT department as participants. The results indicated an improvement in students’ understanding of the definition, types, and impacts of bullying, particularly verbal bullying. Students also demonstrated increased awareness of respectful language use. These findings indicate that language-based educational counseling is effective in supporting bullying prevention efforts in schools.